A multi-agent-based negotiation system for web service selection. (2016) - Bellakhal, Raja; Ghédira, Khaled
The web service selection is the process of finding matches between the service descriptions and the client's specific needs including the QoS parameters. Actually, these parameters are dynamic and considering them static affects negatively the system's reliability. To make dynamic the QoS parameters, negotiation appears a relevant tool as it positively influences the success rate of the web service selection process. However, existing works do not consider important characteristics of the real humans' interactions including dependencies existing between the concurrent negotiation processes, and the hybrid as well as the dynamic negotiation aspects. In this paper, we show that omitting these aspects while implementing a selection system incurs degradation on its performance. We propose a web service selection agent system based on a hybrid negotiation that solves these drawbacks. The experimental results show that the proposed approach outperforms the existing approaches in terms of the outputs quality and the CPU time.